Gratian and the schools of law, 1140-1234 - Kuttner, Stephan 1907-1996; Landau, Peter 1935-2019 (London New York Routledge, 2018)
Cover; Half Title; Title Page; Copyright Page; Table of Contents; Preface; Preface to the Second Edition; 1. The Scientific Investigation of Medieval Canon Law: The Need and the Opportunity in: Speculum 24 (Cambridge, Mass. 1949); 2. Graziano: L'uomo e l'opera in: Studia Gratiana 1 (Rome 1953); 3. Zur Frage der theologischen Vorlagen Gratians in: Zeitschrift der Savigny-Stiftung für Rechtsgeschichte, Kan. Abt. 23 (Weimar 1934); 4. New Studies on the Roman Law in Gratian's Decretum in: Seminar: An annual extraordinary number of The Jurist 11 (Washington, D.C. 1953).
Keywords: Gratian -- active 12th century; Gratian *12th cent.*; Canon Law -- History; Gratian ; active 12th century; Canon law ; History; HISTORY ; General